2022
DOI: 10.1038/s41598-022-09362-y
|View full text |Cite
|
Sign up to set email alerts
|

Oligocene moisture variations as evidenced by an aeolian dust sequence in Inner Mongolia, China

Abstract: The aridification of Central Asia since the Eocene has widespread evidence, but climate-controlled environmental reorganizations during the Oligocene remain ambiguous. We employed environmental magnetic, mineralogical and geochemical methods on a latest Eocene to late Oligocene terrestrial sequence in Inner Mongolia, China, to examine how global climatic trends and regional factors influenced the evolution of moisture and weathering in the region. Highlighting the climatic influence, our weathering and rainfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 113 publications
(183 reference statements)
2
22
1
Order By: Relevance
“…Our ODED CIA data have the expected characteristics of eolian deposition from the Asian interior, similar to coeval Inner Mongolian dust deposits (Supplementary Fig. 5) 49 . These characteristics include (a) a nearly parallel distribution along the CN-Al (CaO*+Na 2 O-Al 2 O 3 ) trend, which suggests weak K-metasomatism (K 2 O) and negligible diagenetic influences 43,44 , and (b) the same value range as Mongolian deposits across the EOT, which suggests an absence of obvious sorting influence.…”
Section: Resultssupporting
confidence: 69%
“…Our ODED CIA data have the expected characteristics of eolian deposition from the Asian interior, similar to coeval Inner Mongolian dust deposits (Supplementary Fig. 5) 49 . These characteristics include (a) a nearly parallel distribution along the CN-Al (CaO*+Na 2 O-Al 2 O 3 ) trend, which suggests weak K-metasomatism (K 2 O) and negligible diagenetic influences 43,44 , and (b) the same value range as Mongolian deposits across the EOT, which suggests an absence of obvious sorting influence.…”
Section: Resultssupporting
confidence: 69%
“…Ulantatal in Nei Mongol is another important site. Recently, Wasiljeff et al (2020) derived a chronostratigraphic framework for the Ulantatal sequence, using paleomagnetic reversal stratigraphy and biostratigraphic correlation, and the time spanned by the strata was 35 to 27 Ma (from the latest Eocene to late Oligocene). The rodents in the lower part of the Kekeamu section in Ulantatal were representative of the latest Eocene (Wasiljeff and Zhang, 2022).…”
Section: Ergilian Rodent Assemblagementioning
confidence: 99%
“…Based on earlier research in the area, the Ulantatal sequence was considered to be constrained to the Oligocene (Wang, 1997b;Gomes Rodrigues et al, 2014). Recently, Wasiljeff et al (2020) redefined the stratigraphy and suggested that the Ulantatal Formation spans from the latest Eocene to the late Oligocene. Here, the Hsandagolian rodent assemblage in the Ulantatal area has been revised based on the latest work.…”
Section: Hsandagolian Rodent Assemblagementioning
confidence: 99%
“…The Ulantatal dust sequence covers the Eocene‐Oligocene Transition (EOT; c. 34 Ma), which marks the dramatic global shift from warmhouse to coolhouse state as permanent ice sheets appeared on Antarctica (e.g., Coxall et al., 2005; Westerhold et al., 2020) and may have stabilized in eastern Greenland (Tripati & Darby, 2018). While there are sites (Xining, Lanzhou, and Weihe Basins) in Central‐East Asia that record the EOT as an episode of significant drying (Abels et al., 2011; Ao et al., 2020; Dupont‐Nivet et al., 2007; Y. Wang et al., 2023), the climate in Ulantatal remained remarkably stable through the transition (Wasiljeff et al., 2022). Rather, major aridification events in Ulantatal are recorded in precipitation proxies after the EOT, at c. 31 and 28 Ma, roughly corresponding to the Early Oligocene Aridification Event (EOAE) and the Mid‐Oligocene Reorganization of fauna in Central Asia (Harzhauser et al., 2016), respectively (Wasiljeff et al., 2022).…”
Section: Introductionmentioning
confidence: 99%